2016
DOI: 10.1166/jbn.2016.2192
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion and Growth on the Anodized Aluminum Oxide Membrane

Abstract: Nanotopological cues are popular tools for in vivo investigation of the extracellular matrix (ECM) and cellular microenvironments. The ECM is composed of multiple components and generates a complex microenvironment. The development of accurate in vivo methods for the investigation of ECM are important for disease diagnosis and therapy, as well as for studies on cell behavior. Here, we fabricated anodized aluminum oxide (AAO) membranes using sulfuric and oxalic acid under controlled voltage and temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…When the pores are smaller than this critical size, the AAO surface is not favorable for cell adhesion but does not induce cell death. These are generally in agreement with the related literature works . For instance, Song et al .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…When the pores are smaller than this critical size, the AAO surface is not favorable for cell adhesion but does not induce cell death. These are generally in agreement with the related literature works . For instance, Song et al .…”
Section: Resultssupporting
confidence: 93%
“…Park et al . showed that AAO does not have any cell toxicity and that cell proliferation is enhanced as the pore size increases up to 30 nm but larger pores (40 nm) decreases the enhancement effect . On the contrary, Taxis et al .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In their case, cells cultured on 30 nm sized nanoporous surfaces proliferated much better than those on flat surfaces and other nanoporous surfaces (40, 45, and 50 nm). Park et al (2016) fabricated anodic aluminum oxide (AAO) membranes, which were designed to possess three different pore sizes, AAO-1 ($25 nm), AAO-2 ($33 nm), and AAO-3 ($46 nm). AAO-1 membranes bearing small sized pores were found to maintain the spreading shape of the cultured cells, while cells cultured on AAO-2 and AAO-3 membranes, bearing large pore-sized AAO membranes, changed shape from spreading to rounding.…”
Section: Nanoporesmentioning
confidence: 99%
“…However, the duration of release is dependent on the amount of protein loaded and the bioactive molecules in the coating; that is, it is limited. Therefore, Rough surfaces, especially nanostructured surfaces, maintain neuron viability more effectively than smooth surfaces, presumably because the former mimic the extracellular matrix [8,9]. Various nanostructured surfaces-such as nanowire arrays [10,11], nanopatterned poly-ε-caprolactone (PCL) [12], and a nanoporous gold (np-Au) substrate [13]-increased neuronal growth compared with that on a flat surface.…”
Section: Introductionmentioning
confidence: 99%